Neutralizing activity of a third dose of CoronaVac against Omicron subvariants within a 20-month follow-up study - Cheng Cao; Qin Guo; Yaping Dai; Junfeng Jiang; Min Liu; Tuo Ji; Pengcheng Zhou; Fang Gong (Human Vaccines & Immunotherapeutics, 2023)
The durability of antibody responses induced by the three-dose of CoronaVac vaccination, especially against SARS-CoV-2 Omicron subvariants, remains unclear. Here in our study, 160 plasma samples from 32 healthy individuals who received three doses of CoronaVac were longitudinally tracked for a period of 20 months. The results showed that a third homologous dose of CoronaVac efficiently increased the SARS-CoV-2 IgG and neutralizing antibody titers and enhanced neutralization activity against Omicron subvariants. The levels of IgG and neutralizing antibody declined from peak levels but remained detectable in most subjects over the course of the next 10–12 months. However, most of the individuals kept neutralizing titers against ancestral Wuhan-Hu-1, while they lost their neutralizing activities against Omicron B.1.1.529, BA.2, BA.4/BA.5, and BA.2.75.2 subvariants at 10–12 months post the third vaccination. Our results suggest that a fourth dose of vaccine may be necessary for uninfected individuals to confer higher neutralization against emerging Omicron subvariants.